Avaliação das relações abundância-biomassa e peixevariáveis limnológicas das assembléias de peixes de riachos, alto da bacia do Rio Paraná, Goiás - Amaral, Rafael Braga do (2012)
In this study the fish assemblage of 27 streams of first and second order were evaluated considering the relationship fish abundance-biomass and fish-limnological variables. The tributaries sampled were located in rivers Piracanjuba (13 streams), Santa Maria (7), Meia Ponte (7). All streams are located in the Upper Paranaíba River basin, Goiás State, where the main activity is cattle ranching. Samplings were conducted between May and September 2009 using the electrofishing method along stretches of 100m in length. A total of 2.161 specimens were captured and they belonged to 6 orders, 18 families and 49 species. At the basin level, ABC curves indicated that any of three basins sampled (Meia Ponte, Piracanjuba and Santa Maria rivers) present disturbance, that is, biomass curve is situated above abundance one indicating the predominance of k-strategists species. On the other hand, when streams are considered individually it was observed that 25.9% suffered disturbance and 74.1% did not. The co-inertia analysis revealed that conductivity, pH, turbidity, phosphate and dissolved oxygen structured fish assemblages in two major axes. Results found suggest that disturbance is diluted when considered the basin but it is more evident at local scale (streams), suggesting the influence of soil use.